HUBUNGAN STATUS GIZI DENGAN HASIL BELAJAR PENJASORKES SISWA KELAS V SDN 004 PULAU BIRANDANG KECAMATAN KAMPAR TIMUR - Rosnah '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. This research has a problem based on observation in SDN 004 Pualu Birandang Kecamatan Kampar Timur. Researcher found that learning outcomes of students is not good enough, almost students can not reach the KKM. This conducted because of nutrition status students in SDN 004 Pulau Birandang Kampar Timur Disctrict. Purpose of this experiment to found out correlation between nutrition status learning outcomes students class V of SDN 004 Pulau Birandang. Type in this research is correlational, and population is all students class V SDN 004 Pulau Birandang amount 18 persons. Total sampling technique used as to get sample for this study as many as 18 persons. Data collected by measuring high and weigh on sample. Analiysis data by correlation product moment.Based on the results of research that has been described in the previous chapter, it can be concluded that there is a relationship of nutritional status to learning outcomes penjasorkes fifth grade students of SDN 004 Birandang Island district. Kampar East , where the result of the correlation rhitung > rtabel . For the results of the nutritional status as classified , namely the category of very thin.Key words : Nutrition Status, Learning Outcomes